MEGA-ORGANIZATIONS AS A TRANSFORMATION TOOL: A REVIEW ON ISTANBUL - Bickici, Didem; Turkun, Asuman (VARAZDIN DEVELOPMENT & ENTREPRENEURSHIP AGENCY, 2018)
Economic activities seem to have become more competitive, world-wide and more complex since the 1980s. With the emergence of globalization, especially in the post-1980 period, the increasing levels of capital circulation, the acceleration of the flow of information and developments in communication and transportation technologies have led to radical socio-economic and spatial transformations throughout the world. Unlike previous periods, global and local capital, together with the initiative of the local governments, have attempted to raise the competitive position of urban areas in the global hierarchy by investing on their underutilized fields to gain a particular identity so as to attract capital and qualified labor. In this process, it is seen that the positions and the roles of cities in the global sphere have changed dramatically with these efforts. It is observed that cities have emerged as focal points that can compete with other cities globally, independently of their countries and boundaries. The spatial requirements of newly emerging service sectors, including especially tourism and qualified production services as well as the intension of increasing capital accumulation by means of real-estate and construction sectors have led to the socio-spatial restructuring of urban areas to a great extent. This survey was developed to monitor the impact of transformational practices of such international organizations, which result in the restructuring of cities generally by means of large-scale projects. The research focuses on locating the positive impacts of megaorganizations on urban transformation practices from many respects, which includes the socio-economic, cultural and spatial dimensions. It is generally observed that those megaorganizations tend to change the hierarchical position and role of urban areas by increasing their attractiveness and competitive position globally but at the same time make life more difficult especially for the local population with limited financial and social resources.
Keywords: City Branding and Identity; Culture Industry; Global City; Mega-Organization; Urban Image; URBAN; GENTRIFICATION; REGENERATION; CITIES; Science & Technology - Other Topics; Business & Economics; Public Administration